Zarlinov nauk o kontrapunktu in antična glasbena teorija - Sukljan, Nejc (Muzikološki zbornik, 2023)
This paper discusses connections between Gioseffo Zarlino’s theory of counterpoint and the ancient theoretical tradition. Basic definitions and the placement of the theory of counterpoint in the broader context of Zarlino’s treatise Harmonic Institutions (Le istitutioni harmoniche, 1558) are followed by examples of various rules of counterpoint: the use of dissonances, the use of the fourth, the characteristics of minor and major thirds, the use of chromaticism and enharmony, and rules for setting text to music.
Keywords: antika; Antiquity; counterpoint; Glasbena teorija; history of music theory; Kontrapunkt; Renaissance; renesansa; Zarlino, Gioseffo; zgodovina glasbene teorije